2015
DOI: 10.1136/archdischild-2014-307157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emollient therapy on clinical outcomes in preterm neonates in Pakistan: a randomised controlled trial

Abstract: NCT01396642.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 24 publications
1
48
2
1
Order By: Relevance
“…Interestingly, a more recent study from Germany shows that sunflower seed oil massage can impair skin barrier maturation and increase TEWL . Topical coconut oil application has also shown a benefit in maintaining skin integrity and reducing the risk of bloodstream infections in a Pakistani study . However, not all oils should be used for maintenance of skin barrier integrity.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a more recent study from Germany shows that sunflower seed oil massage can impair skin barrier maturation and increase TEWL . Topical coconut oil application has also shown a benefit in maintaining skin integrity and reducing the risk of bloodstream infections in a Pakistani study . However, not all oils should be used for maintenance of skin barrier integrity.…”
Section: Resultsmentioning
confidence: 99%
“…In a quasi-experimental study from Pakistan, nurses gave 258 preterm neonates coconut oil massages twice daily that were then continued by their mothers at home for the first month of life (Salam, Darmstadt, & Bhutta, 2015). Data collected by a researcher who was "blind to group assignment" suggested that the mean weight gain was 11.3 grams greater for the massaged newborns as compared to the control group.…”
Section: Preterm Newborn Massage Therapy Effectsmentioning
confidence: 99%
“…A recent trial of oil massage of preterm infants with coconut oil has produced similar results. 79 While an emollient appears to work by preserving skin integrity and protecting from skin injury, 80,81 this intervention is also hypothesized to work by helping accelerate maturation of skin-barrier function (partially through reducing cutaneous signs of essential fatty acid deficiency), thereby reducing likelihood of transcutaneous acquisition of invasive pathogens. Ongoing randomized community-based trials are addressing these questions in large rural populations in Nepal and India.…”
Section: Topical Emollient Therapymentioning
confidence: 98%